Amounts Mobilised from the Private Sector by Official Development Finance Interventions Guarantees, syndicated loans, shares in collective investment vehicles, direct investment in companies, credit lines - Benn, Julia (OECD Development Co-operation Working Papers, 2017)
This working paper presents the results of the 2016 OECD-DAC Survey on amounts mobilised from the private sector in 2012-2015 by official development finance interventions, in particular in the form of guarantees, syndicated loans, shares in collective investment vehicles, direct investment in companies and credit lines. The results indicate that during 2012-2015 USD 81.1 billion was mobilised from the private sector, mainly through guarantees for which the amounts mobilised represented 44% of the total. They also show that most of the amounts mobilised supported projects in middle-income countries (77%), especially in Africa which was the main beneficiary region (30%)